To find fog x in function composition, you will first need to understand what f and g represent. Here, f and g are two functions, and fog (read as ‘f of g’) means you will substitute g(x) into f.
Let’s break down the steps:
- Evaluate g(x): Start by finding the value of g(x) for the given x.
- Substitute into f: Use the result from step one and substitute it into the function f, which gives you f(g(x)).
For example, if f(x) = 2x and g(x) = x + 3, to find fog x, you would:
- Calculate g(x) = x + 3.
- Substitute into f: f(g(x)) = f(x + 3) = 2(x + 3) = 2x + 6.
So, fog(x) = 2x + 6.
This process shows how function composition works. Always remember that the order of composition matters: fog is not necessarily the same as gof.